Potential mitochondrial diversity role in the productivity of three lines of Japanese quails - TAMADHUR HUSSEIN; Mohammed Baqur Al-Shuhaib; TAHREER M. AL-THUWAINI (Society for Indonesian Biodiversity, 2020)
Abstract. Hussein TH, Al-Shuhaib MBS, Al-Thuwaini TM. 2020. Potential mitochondrial diversity role in the productivity of three lines of Japanese quails. Biodiversitas 21: 2258-2265. This study was conducted to identify the mitochondrial D-loop genetic diversity in three lines of Japanese quails that differ in productive performance. A total of 223 quails consisting of 54, 84, and 85 of black (control line), white (egg-producing line), and brown (meat-producing line) quails respectively were genotyped by PCR-single strand conformation polymorphism (SSCP). The genetic and phylogenetic differences within and among quails’ populations were analyzed. Three different SSCP banding patterns were observed in black and brown quails, while white quails exhibited six different SSCP-banding patterns. Sequencing reactions confirmed the presence of 12 haplotypes with 48 variations distributed among the studied birds. The white line exhibited the most diverse nucleotide variability, followed by the brown, and black lines respectively. The mean diversity for all populations was mainly due to within-population variation (71.6%), while among-population variation accounted for much less value (28.4%). Tajima’s D test showed significant values for both productive white (2.45680) and brown (3.07723) lines. In conclusion, this study suggested a wide nucleic acid variation in the investigated egg productive line than the meat productive line respectively compared with the black line control, implying a positive correlation between mitochondrial variability and productive performance.